Protein Disulfide Isomerase Modulates the Activation of Thyroid Hormone Receptors - Campos, Jessica L. O.; Doratioto, Tabata R.; Videira, Natalia B.; Ribeiro Filho, Helder V.; Batista, Fernanda A. H.; Fattori, Juliana; Indolfo, Nathalia de C.; Nakahira, Marcel; Bajgelman, Marcio C.; Cvoro, Aleksandra; Laurindo, Francisco R. M.; Webb, Paul; et al. (Frontiers in Endocrinology, 2019)
Abstract Thyroid hormone receptors (TRs) are responsible for mediating thyroid hormone (T3 and T4) actions at a cellular level. They belong to the nuclear receptor (NR) superfamily and execute their main functions inside the cell nuclei as hormone-regulated transcription factors. These receptors also exhibit so-called ‘nonclassic’ actions, for which other cellular proteins, apart from coregulators inside nuclei, regulate their activity. Aiming to find alternative pathways of TR modulation, we searched for interacting proteins and found that PDIA1 interacts with TRβ in a yeast two-hybrid screening assay. The functional implications of PDIA1 - TR interactions are still unclear; however, our co-immunoprecipitation (co-IP) and fluorescence assay results showed that PDI was able to bind both TR isoforms in vitro. Moreover, T3 appears to have no important role in these interactions in cellular assays, where PDIA1 was able to regulate transcription of TRα and TRβ-mediated genes in different ways depending on the promoter region and on the TR isoform involved. Although PDIA1 appears to act as a coregulator, it binds to a TR surface that does not interfere with coactivator binding. However, the TR:PDIA1 complex affinity and activation are different depending on the TR isoform. Such differences may reflect the structural organization of the PDIA1:TR complex, as shown by models depicting an interaction interface with exposed cysteines from both proteins, suggesting that PDIA1 might modulate TR by its thiol reductase / isomerase activity.